Prophetism-Based Digital Storytelling Training for Literacy and History Empowerment at Al-Maa’uun Orphanage - Ilham Rabbani; Agung Nugroho; Eko Muharudin; Rendi Marta Agung; Bayu Dwi Cahyono; Umi Roisatul Mukaromah (CV. Tripe Konsultan, 2026)
The rapid advancement of digital technology often traps the younger generation in consumptive media use that lacks educational substance. This community service program aims to strengthen digital literacy and historical awareness among the foster children of Al-Maa'uun Orphanage in Wangon, Banyumas, through prophetism-based digital storytelling. Grounded in Muhammadiyah's prophetic values—humanization, liberation, and transcendence—the program utilized direct mentoring and structured training. Conducted in February 2026, the implementation involved twenty-seven children and three caregivers over two face-to-face sessions. The method encompassed historical internalization, short scriptwriting, and technical video production using smartphones and accessible editing software. The evaluation, utilizing pre-testing, post-testing, and interviews, revealed a significant escalation in the participants' cognitive capacity, self-confidence, and digital literacy skills. The children successfully produced and published short, meaningful audio-visual works that encapsulated local historical narratives and Islamic virtues. Ultimately, this empowerment initiative effectively transformed digital devices from mere entertainment tools into strategic cultural instruments. It established a resilient digital literacy ecosystem within the orphanage, enabling the children to actively participate in cultural preaching and ensuring the preservation of the institution's collective memory amidst the modern digital landscape.The rapid advancement of digital technology often traps the younger generation in consumptive media use that lacks educational substance. This community service program aims to strengthen digital literacy and historical awareness among the foster children of Al-Maa'uun Orphanage in Wangon, Banyumas, through prophetism-based digital storytelling. Grounded in Muhammadiyah's prophetic values—humanization, liberation, and transcendence—the program utilized direct mentoring and structured training. Conducted in February 2026, the implementation involved twenty-seven children and three caregivers over two face-to-face sessions. The method encompassed historical internalization, short scriptwriting, and technical video production using smartphones and accessible editing software. The evaluation, utilizing pre-testing, post-testing, and interviews, revealed a significant escalation in the participants' cognitive capacity, self-confidence, and digital literacy skills. The children successfully produced and published short, meaningful audio-visual works that encapsulated local historical narratives and Islamic virtues. Ultimately, this empowerment initiative effectively transformed digital devices from mere entertainment tools into strategic cultural instruments. It established a resilient digital literacy ecosystem within the orphanage, enabling the children to actively participate in cultural preaching and ensuring the preservation of the institution's collective memory amidst the modern digital landscape.